EFEKTIFITAS BIOFILTER DENGAN MEDIA KONTAK BATU VULKANIK UNTUK MENGOLAH EFLUEN AIR LIMBAH DOMESTIK 1 PADA TANGKI SEPTIK KONVENSIONAL - Wardiha, Made Widiadnyana; Prihandono, Aris (Bumi Lestari, 2016)
Biofilter septic tank is one of the domestic wastewater treatment technology uses contactmedia in processing wastewater. Contact media that can be used made from plastic or localmaterial such as volcanic scoria. This research is an applied research in order to test theefectiveness of volcanic scoria as contact media. Location of this research is Badung Regency,Bali. Research conducted by built biofilter wastewater treatment unit at research locationthat have been selected by doing first step that is designing biofilter septic tank in accordancewith the location and teoritically. Wastewater from conventional septic tank at researchlocation flowed into biofilter tank and left in the certain time to grow the biofil which willprocess the wastewater. In certain time, wastewater quality was tested and counted thedecrease percentage of wastewater concentration content. The research result showed thatthe biofilter septic tank is not effective to treat wastewater effluent from conventional septictank because it can only reduce the concentration of wastewater content about 48,74%.The parameters that not comply the wastewater standard such as free ammonia, BOD5, andCOD were reduced each about 82.15%, 45.61%, and 46.04%.
Keywords: septic tank, biofilter, volcanic scoria, wastewater, efectiveness